Patients' knowledge and attitudes to the Wise List - a drug formulary from the Stockholm Drug and Therapeutic committee - Pia Bastholm-Rahmner; Lars L. Gustafsson; Kristina Aggefors; Kristina Ateva; Susanne Elfving; Jaran Eriksen; Malena Jirlow; Maria Juhasz-Haverinen; Rickard E. Malmström; Mahan Nikpour-Ardaly; Magnus Röjvall; Martina Vallin; et al. (BMC, 2018)
Abstract Background Involving patients in decisions about their pharmacotherapy is crucial for a satisfactory treatment outcome. Information and opinions about medicines are available from a variety of sources. The Wise List is the drug formulary of recommended essential medicines for the Stockholm healthcare region and is issued by the Drug and Therapeutics Committee (DTC). To inform the public about treatment for common diseases and the concept of recommended medicines, a patient edition of the Wise List was developed. The aim of this study was to explore patients' knowledge, needs and attitudes to the Wise List, DTC and information about medicines in general. Methods To examine patient knowledge about recommended medicines a survey (n = 312) was carried out at four large primary healthcare centres in Stockholm, Sweden. To further elucidate the patients' needs of the information on recommended medicines and medicines in general, three focus group discussions (FGDs) were performed. Results Of the respondents 57% did not recognise the Wise List, 26% recognised but did not use it and 17% used it. A total of 63% reported that they search for information about medicines. The most common information source was "asking their doctor" (36%) followed by searching the internet (31%). The FGDs revealed that the patients were not interested in medicines in general, only in the medicines they use themselves. They did not understand the aim of the Wise List or how they could benefit from information about recommended medicines. The patients expressed a wish to access all information they need about their own care as well as public healthcare information at one location. Conclusion The intended aim of the DTC with providing information to the public was not achieved as the patients have difficulties to understand the information and how they should use it. The patients were not interested in medicines in general, they wanted information tailored to their specific needs. The findings highlight the importance of creating tools for patients in collaboration with them and evaluate the concept continuously.